2013
DOI: 10.1016/j.jclepro.2013.03.032
|View full text |Cite
|
Sign up to set email alerts
|

The role of water auditing in achieving water conservation in the process industry

Abstract: 22Water has traditionally been over utilised within the process industry due to its low cost. However, 23 increasing environmental regulations, concerns around human and ecological health, and consumer 24 expectations of high environmental performance have placed water conservation onto the agenda of 25 the process industry. Many conceptual and mathematical techniques are available for determining 26 appropriate water management practices to achieve this, but these are often not easily applied in 27 complex, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Moreover, the analysis of the outcomes of the undertaken social survey helped in identifying thresholds of feasible IBT scenarios, while retracting tariff options which received a negative feedback. The inclusion of social aspects in this modelling exercise is deemed crucial, since raising awareness to achieve behavioural changes is as important as technical design and calculations when aiming at water conservation and minimisation (Barrington et al, 2013). It is important to highlight how this study focuses solely on water delivered by the water utility to the households.…”
Section: Approachmentioning
confidence: 99%
“…Moreover, the analysis of the outcomes of the undertaken social survey helped in identifying thresholds of feasible IBT scenarios, while retracting tariff options which received a negative feedback. The inclusion of social aspects in this modelling exercise is deemed crucial, since raising awareness to achieve behavioural changes is as important as technical design and calculations when aiming at water conservation and minimisation (Barrington et al, 2013). It is important to highlight how this study focuses solely on water delivered by the water utility to the households.…”
Section: Approachmentioning
confidence: 99%
“…Likewise, sourcing from suppliers located in regions where local water scarcity is low (Huang et al, 2014), as well as changing the composition of the final food commodities aiming to contain water-friendly raw materials (Jeswani et al, 2015), could further reduce the total product WF. As regards internal industrial operations, the establishment of internal WF auditing (Ene et al, 2013) and control (Tsolakis et al, 2014) systems is necessitated in order to identify processes generating water losses and define methods for wastewater reduction (Barrington et al, 2013). It is also suggested that manufacturers should invest in water-efficient technologies that consume lower volumes of freshwater during processing (McKinsey and Company, 2009).…”
Section: Sustainable Practices For Water Footprint Mitigationmentioning
confidence: 99%
“…1) was implemented to all the participating plants in this study (Barrington et al, 2013). Water balance charts were distributed and collected for all the participating plants.…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…In the process system, it may be possible to cascade reuse wash or rinse water through processes with various water quality requirement, as the effluent becomes cleaner as it progresses downstream (Eble and Feathers, 1992). This step involves a thoughtful analysis of water quality requirements for each process, as well as the actual effluent water quality at each step (Barrington et al, 2013). In some cases, partial of the effluent streams can be reused after regeneration unit, depending on the assessment results from laboratory-scale trials for types of treatment process (e.g.…”
Section: Synergistic Effect and Water Recycling Strategiesmentioning
confidence: 99%